(untitled) (Pedagogical Horizons, 2024)
As part of the "HoFo meets PHforscht" study day at the Private University College of Teacher Education of the Diocese of Linz on the topic of "Blended learning in teacher training (initial, further and continuing education), the concept of a course for primary school teacher training was presented, which is designed as a blended learning event with synchronous and asynchronous phases. There is a particular focus on diversity-sensitive university teaching, cooperative and self-organised as well as sustainable learning. Feedback shows that the variety of methods, flexibility in terms of time and location and individualisation in particular have contributed to the success of this virtual blended learning course.